Optimal cluster head selection and rotation of cognitive wireless sensor networks for simultaneous data gathering and long life system. (December 2017) - Takyu, Osamu; Fujii, Shohei; Akimoto, Youhei; Ohta, Mai; Fujii, Takeo; Sasamori, Fumihito; Handa, Shiro
Simultaneous data gathering is an application that exploits the unique advantages of wireless sensor networks. Because many sensor nodes access a channel, co-channel interference limits the number of nodes who can access it. To suppress co-channel interference, a frequency spectrum (or channel) is required to obtain large diversity and spreading gains. Cognitive radio with transmit power control exploits available channels because, in this approach, the co-channel interference on the primary system is suppressed and spectrum sharing between the primary system and a secondary system is possible. Prolonging a node's life is also important in wireless sensor networks. However, in simultaneous data gathering, the power consumed by the relay station (cluster head) is quite high. In this article, a method for constructing a cluster head selection and rotation that is optimal for increasing the number of available channels and prolonging the life of the node is proposed. In simultaneous data gathering, the link with the minimum number of available channels is the bottleneck. Our proposed technique achieves the maximum number of available channels and extends the life of the nodes because of the cluster head rotation. In addition, the optimal number of clusters is also determined.